Epirubicin dose and sequential hormonal therapy—Mature results of the HMFEC randomised phase III trial in premenopausal patients with node positive early breast cancer. (June 2016) - Coombes, R.C.; Kilburn, L.S.; Tubiana-Mathieu, N.; Olmos, T.; Van Bochove, A.; Perez-Lopez, F.R.; Palmieri, C.; Stebbing, J.; Bliss, J.M.
Abstract: Background: The hormonal manipulation 5-Fluoro-uracil Epirubicin Cyclophosphamide (HMFEC) trial was developed at a time of uncertainty around the dose intensity of chemotherapy given to premenopausal patients with node positive breast cancer and to the benefits of tailored endocrine therapy in such patients. Patients and methods: HMFEC was a multi-centre, phase III, open label, randomised controlled trial with a 2 × 2 factorial design. Eligible patients were premenopausal with node positive early breast cancer; significant cardiac disease or uncontrolled hypertension was exclusion criterion. Patients were allocated to receive either eight cycles of FE50 C or FE75 C (given 3 weekly) with or without hormone manipulation (HM; tamoxifen or luteinising hormone releasing hormone (LHRH) agonists according to residual hormone levels at the end of chemotherapy) irrespective of ER status. The primary end-point was disease free survival (DFS). Principal analyses were by intention to treat (ITT); however, to reflect contemporary practice, subgroup analyses according to ER status were also conducted. The mature follow-up now available from this modest sized trial enables presentation of definitive results. Results: Between 1992 and 2000 a total of 785 patients were randomised into the HMFEC trial (203 FE50 C−HM, 191 FE50 C+HM, 198 FE75 C−HM, 193 FE75 C+HM). At a median follow-up of 7.4 years, 245 DFS events have been reported (92 ER−, 153 ER+/unknown). The effects on DFS were not statistically significantly different according to epirubicin dose (hazard ratio [HR] = 0.82, 95% confidence interval [CI] 0.63–1.06; p = 0.13 FE75 C versus FE50 C); however, FE75 C appeared to induce more alopecia and neutropenia. No statistically significant evidence was observed to support an improvement in DFS in patients allocated HM either overall (HR = 0.88, 95% CI 0.68–1.13; p = 0.32) or in patients with ER+/unknown disease (HR = 0.85, 95% CI 0.62–1.17; p = 0.32) although effect sizes are consistent with worthwhile clinical effects. Overall, there was no evidence of a difference in survival between any of the four treatment groups of the trial. Conclusion: Higher doses of epirubicin cause more adverse events in the absence of clear improvement in overall survival. Endocrine therapy with either tamoxifen or goserelin provided no significant added benefit to cytotoxic chemotherapy in this group of patients. Trial Registration Number:ISRCTN98335268 Highlights: In premenopausal node positive breast cancer FEC (75) caused more adverse effects than FEC (50) but showed similar effects on overall survival. Endocrine therapy, in the form of either tamoxifen or goserelin, provided no significant added benefit to cytotoxic drugs in this group of patients.